Social Support Mediates the Relationship between Mindfulness, Life Satisfaction, and Loneliness among Foreign Students - Al-Dbyani, Aamer Mohammed; Lv, Yiqing; Merkine, Bereket; Qiao, Xiuqing; Atta Ullah (Journal of Educational and Psychological Sciences, 2021)
Loneliness and life satisfaction are important indicators of people's mental health. The study found that Mindfulness plays an important role in improving Life Satisfaction and reducing Loneliness, but the underlying mechanism is unknown. This study examined the relationship between Mindfulness, Life Satisfaction, and Loneliness and the potential mediating of Social Support among foreign students in China. Yemeni students of the Chinese Universities during Academic Year 2020 (N = 509) were surveyed to determine levels of Mindfulness, Social Support, Life Satisfaction, and Loneliness.The study found that all the five dimensions of mindfulness are positively predicting the three dimensions of social support, and only the perceived support of friends can one experience life satisfaction, and only the perceived support of significant others can reduce loneliness.
Keywords: Social Support; Mindfulness; Life Satisfaction; Loneliness; Foreign students